Metodyka zarządzania projektem w oparciu o praktykę firm logistycznych - Brdulak, Halina (Methods of Project Management Based on the Practice of Logistic Companies, 2008)
Project management is a relatively new approach to management in general, more often used by logistic companies. This concept is used to describe in logistic companies various actions (time-limited, having particular budget and involving a particular number of people) leading to sole, unique changes within products and/or processes. For its realization it is indispensable to create particular project methodology. In logistic companies' case, taking part in large international tenders, this approach is required by a client. Rohling example, which won tender for contractors' service for GM, shows the complex of the above process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 15-27